Phenology and growth performance of Himalayan birch (Betula utilis) in Kashmir Western Himalayas along the different altitudinal gradients - MIR, NASEER A; MASOODI, T H; MIR, ASHFAQ A; KHAN, HINA; SOFI, P A; WANI, FEHIM JEELANI; HAMEED, OMAR BIN (The Indian Journal of Agricultural Sciences, 2016)
The phenological events, height class distribution, volume and biomass of Himalayan birchor bhojpatra (B. utilis D. Don) were monitored along the altitudinal gradient in distinct ecological settings at Sindh and Tangmarg forest divisions in western Himalayas, Kashmir. The observations recorded revealed high synchrony throughout the altitudinal gradients, especially for bud set, bud burst, peak flowering and seed maturation. All the phenological events began early at lower elevation as compared to higher elevation. The timing of phenophases along the altitude was governed by the timing of snow-melt which is usually responsible for early phenological changes in the northern alpine habitats. The height, volume and biomass showed a decreasing trend with increasing altitude at both the sites. Higher number of trees (116.71 trees/ha) with maximum height, volume (112.38 m3/ha) and biomass (57.31 tonnes/ha) were recorded at 3 000-3 200 m asl. The values for all these parameters decreased with increasing altitude from 3 200-3 400 and 3 400-3 600 m amsl, respectively. The short growing seasons, reduced air and soil temperature (an adiabatic effect), increased exposure to wind, lower availability of nutrients and increased exposure to frost are some of the common features of high altitude niches which greatly influences the growth of the existent vegetation.